The impact of workfare income supplement scheme on real income of low-wage workers in Singapore - Gan, Evonne Ern Xing (2011)
With the rich getting richer and the poor getting poorer, the issue of the widening wage gap has been a cause of concern for many developed countries, including Singapore. Some of these countries implemented workfare policies to address this issue. In this study, we investigate how the Workfare Income Supplement scheme affects the real income of low-wage workers from age group 35-44, 45-54 and 55 & above across four occupational groups in Singapore. The analysis is conducted using the difference-in differences estimation based on data retrieved from government publications. Our main result shows that the overall impact is positive across the three age groups, with the youngest having the largest increment and the oldest receiving the least. This implies that the scheme is quite effective in boosting the income of these workers and motivating them to work more.